Visual pollution and noise: a troubled relationship between environment and society - Codato, Marcos Vinicius Ferreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Pollution is considered, all the degradation suffered by the nature caused by the disposal of materials and waste that cause imbalance and changes in the environment, she has become the target of many problems and extreme environmental impacts, due to several factors from among them the lack of proper structuring of society, the lack of technical and specialized professionals who can prevent and control noise pollution and visual pollution in rural areas and urban centers, and the absence of law enforcement and effectiveness of law. This study aimed to conceptualize these two forms of pollution audible and visual aiming stimulate research in this field, such as addressing an environmental issue that requires public health care by everyone, as they are responsible for generating discomfort and damage the quality life of human beings. The generates long-term these discomfort presents characteristics destructive to the society, being necessary to the government, the community and the individuals who belongs to it, fulfill its obligations and make use of their rights, so that through proper attitudes can charge and encourage new generations to live in a more comfortable way.